Reimagining the poetry of B.W. Vilakazi as the social tool for 'ukuxwayisa' (deterrent) and protest - Zondi, Nompumelelo (University of Pretoria, 2022)
Dissertation (MA (Creative Writing))--University of Pretoria, 2021.